ACCOUNTANCY, SYSTEMATIZED LEARNING, AND ECONOMICS. - Flanders, Dwight P. (The Accounting Review, 1961)
The aim of this article first to indicate very broadly the principal areas of systematized learning, and secondly to compare and contrast accountancy and economics within the framework of these areas. Methodology and content are two integrated aspects of any area of systematized learning, so it should be made clear that sometimes dichotomizing accountancy and economic studies into either their content or methodology is merely an analytical device. It has been clarified that economics is mainly concerned with the study of behavior, while accountancy is concerned with the study of the quantification and analysis of the resultants of behavior. Metaphysics may seem a far cry from either accountancy or economic studies, yet the basic postulates of science, including the postulate of the orderliness of natural and social phenomena, stem from metaphysical analysis. Epistemology embraces studies of the nature and criteria of human knowledge, including the role of definitions, postulates, as well as inductive and deductive analyses. Both accountancy and economics have some stake in the development of metaphysics, but much more stake in the development of epistemology. In the area of accountancy the ethics principal is most often that of the practicing accountant. On the other hand, the problem of ethical behavior in economics almost always involves the behavior of others, namely the behavior of the makers of economic policy.